Progress and Change in Post Conflict Developing Regions: Observations of A Longitudinal Grounded Theory Case Study of a Successful Large Scale ICT Adoption in Kosovo. Issue 24 (2015) - Kealy, Anita; Stapleton, Larry
Abstract: Post-conflict regions are extreme situations which load additional variables onto systems engineering projects. Whilst the immediate conflict may be over in a post conflict situation, the effects of the changes in government, infrastructure and society will continue to have an impact on ICT adoptions. This paper builds on previous research on the success factors in a large scale ICT adoption in a developing, post conflict region. Using Lund's Curve of Conflict the changes observed during a longitudinal case study in a successful post-conflict health informatics project are explored. Health informatics technologies are an important response to the difficult conditions in post conflict regions. The primary contribution of this paper is twofold. Firstly, to build on previous work on a case study of a successful Telemedicine Systems implementation in a post conflict region. Secondly, to note the successful navigation of changes in a telemedicine initiative in a post conflict Balkan region. These contributions open up new avenues for research into international stability and advanced technology adoption in post-conflict regions.